Sibling Position and the Development of Social Skills among Children - Molesy, Anthony; Ngyah-Etchutambe, Ijang; Fon, Koi (International Journal of Psychology, 2022)
Purpose: This article examines the role sibling position (birth order) plays in the development of social skills. Given that the family is the first social system a child gets exposed to, it is assumed that the child's birth position and the relationships that exist among family members plays a substantial role in their development of social skills. The paper focuses on three birth positions: first borns, last borns and only child. The study thus aims to examine whether the a fore mentioned birth positions influences a child's tendency to communicate and relate with others. Does one's birth position influence his or her tendency to communicate and relate with others? Methodology: It is a conceptual paper that employs a meta-analytic approach to review, synthesize and draw conclusions from existing literature on sibling position specifically the first born, last born and only child and the effect such positions have on the development of social skills. Findings: It was realized that first borns perceive themselves as being treated differently from later children, are accustomed to being the centre of attention and tend to be high achievers. Last borns are perceived to be creative, outgoing, extraverted, disobedient and tend to resist the authority of the bigger siblings. They exhibit interpersonal skills but have an abnormally strong feeling of inferiority as result of being over pampered by their seniors. Only children are not independent and have difficulty in delaying gratification. They demand much love from their partners with unwillingness to reciprocate. They are also most often self-centred, maladjusted, unlikable, anxious and dependent on others. The degree to which people tend to relate and communicate with others is influenced to some extent by their birth order. Unique Contribution to Theory, Practice and policy: It is thus vital to minimize certain cultural attitudes exhibited by parents, siblings and other family members in the course of socialization at home that can deter the development of social skills in children. This is supported by Bandura's (1978) Theory of Observational Learning, as children learn or model behaviours from especially elderly siblings and other caregivers; Bowlby's (1969/1982) attachment theory which maintains that patterns of relating are built upon the early interactions between the primary caregiver and the child.